2019
DOI: 10.3389/fendo.2019.00694
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Ovulation Trigger–Oocyte Pickup Interval in Progestin-Primed Ovarian Stimulation Protocol: A Retrospective Study Using Propensity Score Matching

Abstract: Background: To investigate the optimal ovulation trigger–oocyte pickup (OPU) interval of a progestin-primed ovarian stimulation (PPOS) protocol.Method: Patients with normal ovarian reserve in their first PPOS OPU cycle were enrolled in this retrospective cohort study between July 2013 and April 2018. This retrospective cohort study included two parts. In part I, we studied the regression trend of mature oocyte rate, implantation rate, and live birth rate within the whole ovulation trigger–OPU interval of 7,258… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…We could only verify the function of PPOS in delaying ovulation from the distribution of ovulation trigger-OPU time intervals with oocyte retrieval rate (> 70%) and mature oocyte rate (> 80%). And the mature oocyte rate and implantation rate of patients using PPOS was signi cantly higher in the groups with prolonged trigger-OPU interval 11 .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…We could only verify the function of PPOS in delaying ovulation from the distribution of ovulation trigger-OPU time intervals with oocyte retrieval rate (> 70%) and mature oocyte rate (> 80%). And the mature oocyte rate and implantation rate of patients using PPOS was signi cantly higher in the groups with prolonged trigger-OPU interval 11 .…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, our former clinical research 11 in patients with PPOS protocol, which used the propensity score to auto-match patients with the homogeneous clinical characteristics among three trigger-OPU interval groups (group 1: 35.6-36.4h; group 2: 36.4-37.1h; group 3: 37.1-37.8 h), found that the trigger-OPU interval within groups 2 and 3 had signi cantly higher mature oocyte rates (84.54% vs. 84.60% vs.82.34%, p = 0.002) and implantation rates (34.17% vs. 34.37% vs. 29.61%, p < 0.05) than group 1. A relative prolonged ovulation trigger-OPU interval (36.4-37.8 h) is optimal for most patients using a PPOS protocol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirdly, the sample size was small, especially in the CC + hMG group. Fourth, the interval between ovulation triggering and oocyte retrieval was not analyzed in the study, but it was crucial to preventing ovulation before the retrieval while ensuring proper maturity of oocytes, especially when there was a premature LH surge [ 43 , 44 ]. Caution is needed when interpreting the results, and future randomized controlled trials with a larger sample size are called for.…”
Section: Discussionmentioning
confidence: 99%
“…injections of hCG (1000–5000 IU). Transvaginal ultrasound-guided oocyte retrieval was conducted 34–36 h after the trigger in the PPOS strategy ( Kuang et al , 2015 ; Wang et al , 2018 ; Yu et al , 2018 ; Shen et al , 2019 ) and at 32–36 h in the LPS protocol ( Kuang et al , 2014 ). All follicles with a diameter greater than 10 mm were aspirated.…”
Section: Methodsmentioning
confidence: 99%